2009
DOI: 10.1007/s12562-009-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary medicinal herbs on lipid metabolism and stress recovery in red sea bream Pagrus major

Abstract: The effect of dietary medicinal herbs on lipid metabolism and stress recovery was investigated in red sea bream Pagrus major. Fish (mean body weight 24.0 ± 0.2 g) were fed on test fish meal diets supplemented with either Massa Medicata (Mm), Crataegi Fructus (Cf), Artemisia capillaries (Ac), or Cnidium officinale (Co), or with a mixture of the four herbs (HM) for 12 weeks. A control group was fed a diet without herbs in the same manner. A high survival rate was observed in the herbal diet groups. The final mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
9
26
0
Order By: Relevance
“…Interestingly, serum lysozyme activity was higher in the treatment group than the control group both before infection and 6 h after infection. Such increases in lysozyme activity have also been noted in red sea bream (Pagrus major) that were fed with Chinese herbs [50] and in freshwater prawns or common carp (Cyprinus carpio jian) fed with anthraquinone extracts [7,13]. Similarly, Su et al [38] reported an increase in serum lysozyme activity following Vibrio anguillarum infection in Macrobrachium rosenbergii that were fed with anthraquinone.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, serum lysozyme activity was higher in the treatment group than the control group both before infection and 6 h after infection. Such increases in lysozyme activity have also been noted in red sea bream (Pagrus major) that were fed with Chinese herbs [50] and in freshwater prawns or common carp (Cyprinus carpio jian) fed with anthraquinone extracts [7,13]. Similarly, Su et al [38] reported an increase in serum lysozyme activity following Vibrio anguillarum infection in Macrobrachium rosenbergii that were fed with anthraquinone.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, any substance that can decrease stress can increase growth in the long term (Jentoft, Aastveit, Torjesen & Andersen 2005). Slight decrease in serum cortisol after air exposure, compared with controls, was seen also in juvenile Pagrus major fed medicinal herb prior to air exposure (Ji, Takaoka, Lee, Hwang, Kim, Ishimaru, Seoka, Jeong & Takii 2009). Slight decrease in serum cortisol after air exposure, compared with controls, was seen also in juvenile Pagrus major fed medicinal herb prior to air exposure (Ji, Takaoka, Lee, Hwang, Kim, Ishimaru, Seoka, Jeong & Takii 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Stress would cause the increase of haemolymph lysozyme [41,42] or the decrease of haemolymph lysozyme activity [8,43,44]. The red sea bream (Pagrus major) fed with Chinese herbs [45] and common carp (C. carpio jian) fed with anthraquinone extract [20] showed the increase of blood lysozyme activities under the stress. This experiment result showed that haemolymph lysozyme activities significantly increased in the treated groups supplemented with 0.1% and 0.4% anthraquinone extract before stress and in the treated group supplemented with 0.4% anthraquinone extract at 12 h after high temperature stress compared to the control.…”
Section: Discussionmentioning
confidence: 99%